Teaching and Learning Against all Odds: A Video-Based Study of Learner-to-Instructor Interaction in International Distance Education - Jean-Marie Muhirwa (Athabasca University Press, 2009)
Distance education and information and communication technologies (ICTs) have been marketed as cost-effective ways to rescue struggling educational institutions in developing countries, particularly in sub-Saharan Africa (SSA). This study uses classroom video analysis and follow-up interviews with teachers, students, and local tutors to analyse the interaction at a distance between learners in Mali and Burkina Faso and their French and Canadian instructors. Findings reveal multiple obstacles to quality interaction: frequent Internet disconnections, limited student access to computers, lack of instructor presence, ill-prepared local tutors, student unfamiliarity with typing and computer technology, ineffective technical support, poor social dynamics, learner-learner conflict, learner-instructor conflict, and student withdrawal and resignation. In light of the near death of the costly World Bank-initiated African Virtual University (AVU), this paper concludes by re-visiting the educational potential of traditional technologies, such as radio and video, to foster development in poor countries.